A Study of the Limno-Chemistry and Plankton Diversity of the Lake Water: Assessing the Limno-Chemistry and Plankton Diversity of Lake Water for Environmental Health Monitoring (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A limnology study of the limno-chemistry and plankton diversity of a lake can provide valuableinformation about the lake's health and ecological balance. Limno-chemistry refers to the chemicalcharacteristics of the lake water, while plankton diversity refers to the variety of microscopic organismsthat live in the water. The first step in conducting such a study would be to collect water samples fromvarious points in the lake, ensuring that the samples are representative of the entire lake. These samplescan then be analyzed for a variety of limno-chemical parameters, including pH, dissolved oxygen levels,nutrient levels (such as nitrogen and phosphorus), and heavy metal concentrations.